ADME and toxicity considerations for tramadol: from basic research to clinical implications. (2nd July 2020) - Doostmohammadi, Mohsen; Rahimi, Hamid-Reza
ABSTRACT: Introduction: Tramadol is widely being used in chronic pain management for improving patients' life quality and reducing trauma. Although it is listed in several medicinal guidelines, its use is controversial because of the conflicting results obtained in pharmacokinetic/pharmacodynamic studies. This multi-receptor drug acts as µ1 opioid receptor agonist, monoamine reuptake inhibitor, and inhibitor of ligand-gated ion channels and some special protein-coupled receptors. Areas covered: This review provides a comprehensive view on the pharmacokinetic, pharmacodynamic, and toxicity of tramadol with a deep look on its side effects, biochemical and pathological changes, and possible drug interactions. In addition, the main ways of tramadol poisoning management describe according to in vivo and clinical trial studies. Expert opinion: Given the broad spectrum of targets, increasing the cases of overdoses and toxicity, and probable drugs interaction, it is necessary to take another look at the pharmacology of tramadol. Regarding the adverse effects of tramadol on different tissues, especially the nervous system and liver tissue, more attentions to tramadol metabolites, their interaction with other drugs, and active agents seem critical. Seizure as the most cited effect of tramadol and its destructive effects on tissues would alleviate by co-administration with drugs with antioxidant properties.